Adipose-derived stem/progenitor cells from lipoaspirates: A comparison between the Lipivage200-5 liposuction system and the Body-Jet liposuction system. Issue 1 (January 2020) - Taha, Sara; Saller, Maximilian Michael; Haas, Elisabeth; Farkas, Zsuzsanna; Aszodi, Attila; Giunta, Riccardo; Volkmer, Elias
Summary: Background: Adipose-derived stem/progenitor cells (ADSPCs) are under investigation in many clinical applications for their regenerative potential in a variety of autoimmune, degenerative, and inflammatory diseases. Adipose tissue, which is mainly harvested by manual liposuction, is the main source of these ADSPCs. Objective: In the past years, a variety of different liposuction devices have been commercialized. To ensure a high quality of obtained ADSPCs, it is crucial to show the advantages and disadvantages of frequently used liposuction methods. For this reason, the objective of this study was to compare ADSPCs harvested by either the suction-assisted LipiVage200-5 or the water-assisted Body-Jet system. Methods: The proliferation potential of ADSPCs, harvested from 20 patients, was assessed by cumulative population doublings (cumPD), population doubling time (PDT), colony-forming units (CFU), and cell metabolism assays. To prove the multipotency of the primary isolated cells, ADSPCs were induced to differentiate into adipogenic, osteogenic, and chondrogenic lineages. Results: Our data show a significantly higher cumPD, as well as a significantly lower PDT for cells obtained by the Body-Jet system. No significant differences were found regarding the CFU efficiency and the cell metabolism. Furthermore, we showed that the adipogenic, osteogenic, and chondrogenic potential of ADSPCs is similar in both groups. Discussion/conclusion: In our study, we provide evidence that the cell characteristics and the functional properties of ADSPCs isolated after liposuction with different techniques are largely similar. However, we observed a significantly higher cumPD and a slightly higher adipogenic potential in cells isolated after liposuction with the Body-Jet system. Different cannula sizes and sheer stresses in the used methods might play a role here.